Use of WhatsApp Technology to Improve Understanding and Self Learning Ability of Engineering Students - Patil, Rajkumar D.; Kabnure, Bahubali B.; Balwan, Vishal R. (Asian Journal of Science and Applied Technology, 2020)
In today’s academic system teaching has become more difficult and learning becomes so far lagging in the students. The students are now resistive with the traditional teaching methods. Some of the difficult concepts cannot be taught by using Chalk and Talk method. So, use of ICT tools and innovative teaching learning pedagogy becomes essential in engineering colleges. But due to lack of sufficient time, all methods cannot be implemented. In this research, WhatsApp technology is used for better understanding and self-learning of the difficult concepts. The impact of this method on the understanding of the participants is also analyzed.